Kiosk and main square, Tampico - García Izaguirre, Víctor Manuel; Universidad Autónoma de Tamaulipas (Libros UAT, 2019)
This book aims to show the work that was developed in conjunction with students and teachers of the fadu and with the municipal and state authorities, to leave the testimony of what was achieved from what had been raised, what was projected both for the kiosk and for the Plaza de Armas de Tampico, a project that, we are Sure, you'll see the light so that the inhabitants of the city can enjoy it. The union of efforts and ideas is presented in subsequent chapters, which summarize what has been done, both by students and by advisors, in the executive project, which covered from November 2012 to August 2013, date in which the second stage was concluded.